2001
DOI: 10.1046/j.1469-8137.2001.00081.x
|View full text |Cite
|
Sign up to set email alerts
|

Ectomycorrhizal protection of Pinus sylvestris against copper toxicity

Abstract: Summary• Change in the copper (Cu) sensitivity of Pinus sylvestris is presented, in response to the ectomycorrhizal fungi, Suillus bovinus and Thelephora terrestris , common mycobionts on metal contaminated sites.• Seedlings grown under phosphorus (P) limitation were exposed to a range of Cu concentrations. Plant and fungal development, P nutrition, sorption of Cu on roots and external mycelia as well as transfer of Cu to shoots were assessed.• Root growth and P nutrition were severely inhibited in nonmycorrhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(44 citation statements)
references
References 44 publications
1
41
0
2
Order By: Relevance
“…At the highest Cu concentration, the Cu/P ratio in NM plants (1.4) was considerably higher than the ratios in mycorrhizal plants (0.4 for the UH-Slu-Fg1.6 isolate and 0.7 for the UH-Slu-Lsk10 isolate), indicating that the fungi are able to maintain a more favorable nutritional status for their pine hosts. In a previous study we found evidence that the ECM fungi S. bovinus and Thelephora terrestris could protect pines from Cu stress (28). In both studies, the ameliorating effect of the ECM fungi on host fitness could be ascribed to better plant nutrition and reduced uptake of Cu.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At the highest Cu concentration, the Cu/P ratio in NM plants (1.4) was considerably higher than the ratios in mycorrhizal plants (0.4 for the UH-Slu-Fg1.6 isolate and 0.7 for the UH-Slu-Lsk10 isolate), indicating that the fungi are able to maintain a more favorable nutritional status for their pine hosts. In a previous study we found evidence that the ECM fungi S. bovinus and Thelephora terrestris could protect pines from Cu stress (28). In both studies, the ameliorating effect of the ECM fungi on host fitness could be ascribed to better plant nutrition and reduced uptake of Cu.…”
Section: Discussionmentioning
confidence: 99%
“…Inoculated and noninoculated plants were divided at random into four Cu treatments to create a factorial setup with the factors Cu treatment (0.1, 15, 30, and 60 M Cu 2ϩ ) and fungal inoculation. This Cu gradient was selected because it results in severe disturbance of tree root functioning in (semi-)hydroponic conditions (26,28). For each combined treatment there were five replicates.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mycorrhizal fungi also modify the interactions of plants with other soil organisms, both pathogenic (nematodes and fungi) as well as mutualists (nitrogen-fixing bacteria) (van Tichelen et al 2001). Pathogenic fungi may invade roots but mycorrhizal fungi alter host response to these pathogens.…”
Section: Protection From Pathogensmentioning
confidence: 99%
“…Numerosos estudios han demostrado la superioridad de las plántulas micorrizadas frente a las no micorrizadas en términos de establecimiento y supervivencia en campo, generando mejores respuestas a los crecimientos en las forestaciones (Gagnon et al 1988 y referencias allí incluidas, Stenström et al 1990, Krasowski et al 1999, Jumpponen 2001, Van Tichelen et al 2001, Dunabeitia et al 2004, Ortega et al 2004. Sin embargo, el manejo de la micorrización bajo sistemas que reciben fertilización requiere un estudio detallado para cada caso, dado que existen reportes contradictorios sobre el efecto inhibidor de la fertilización sobre la micorrización, dependiendo de las especies arbóreas y fúngicas involucradas (Menkis et al 2005).…”
Section: Introductionunclassified